Realism and idealism in foreign policy decision making - Smith, Hayden J. (Lexington Books, 2021)
This book examines the foreign policy decisions of individual US presidents-including Richard Nixon, Jimmy Carter, George W. Bush, Barack Obama, and Donald Trump.